Riba dan Ketidakadilan Sistem Ekonomi Kapitalisme: Sebuah Kajian Teoritis - Yusi Septa Prasetia; Mohammad Ghozali (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2015)
Economic failures of capitalism in the justice and welfare system is due to interest (usury system) has applied. In the long term usurious system pose a huge gap between communities. So that cause various effects on the economy of the people. As the imbalance of the real sector and monetary sector, poverty and others. Islamic Economics as an economic system that re-echoed back to try to achieve justice and prosperity followers to abolish interest (usury) and replacing it with a system of profit sharing (profit loss sharing). As one alternative to achieve economic justice. The underlying revenue sharing system embodiment keadialan in various financial sector and the real sector. In an effort to expunge ribawi the centuries took place in various countries.